Algorithmic aspects of enriched time domain boundary element methods. (March 2019) - Gimperlein, Heiko; Stark, David
Abstract: We discuss the algorithmic aspects of a recently proposed time-domain partition-of-unity boundary element method for wave propagation problems a high frequency on coarse mesh grids. A main challenge is the accurate assembly of the Galerkin matrix for travelling plane-wave basis functions. We discuss the numerical solution of the space-time system and its preconditioning. Numerical results demonstrate the prospects and challenges of the approach.